Spatial Resolution Enhancement of Video Using Still Images - Guo, Guodong; Dyer, Charles (University of Wisconsin-Madison Department of Computer Sciences, 2004)
Images captured by digital video cameras usually have lower spatial resolution than digital still cameras. This paper addresses the problem of combining images from digital still cameras and video cameras to generate a video sequence with higher resolution than the original video. A method is presented for accomplishing this goal and experimental results are shown that demonstrate its effectiveness.